Dielectric properties of mineral oil_based nanofluids under temperature variations - Pichai Muangpratoom; Norasage Pattanadech (My University, 2019)
The aim of this research is to improve the electrical properties of dielectric liquids. An examination of the dielectric properties of mineral oil-based nanofluids was carried out, using three different nanoparticle types: titanium dioxide, zinc oxide, and barium titanate, each with a mean diameter not exceeding 100 nm. The test samples were divided into two groups, including mineral oil mixed with nanoparticles at a concentration of 0.01 and 0.03% volume fraction, respectively. Determination of the AC breakdown voltage of the unmodified mineral oil and the nanofluid samples was performed through testing at temperatures varying within the range of 35–90°C in accordance with the standards of IEC 60156. Furthermore, testing was also performed to determine the dielectric dissipation factor (tanδ) for each of the liquid samples according to IEC 60247. From the study, it was shown that the performance of nanofluid was significantly affected by increasing the temperature. It could be observed from the findings that the use of nanoparticles in creating mineral oil-based nanofluids had potential to bring a number of advantages in terms of dielectric applications.
Keywords: Mineral oil; Titanium Dioxide; Nanofluidics; Power Transformer Diagnostics and Insulation